One-Year Clinical Evaluation of the Bonding Effectiveness of a One-Step, Self-Etch Adhesive in Noncarious Cervical Lesion Therapy. (25th February 2015) - Faye, Babacar; Sarr, Mouhamed; Bane, Khaly; Aidara, Adjaratou Wakha; Niang, Seydina Ousmane; Kane, Abdoul Wakhabe
Abstract : This study evaluated the one-year clinical performance of a one-step, self-etch adhesive (Optibond All-in-One, Kerr, CA, USA) combined with a composite (Herculite XRV Ultra, Kerr Hawe, CA, USA) to restore NCCLs with or without prior acid etching. Restorations performed by the same practitioner were evaluated at baseline and after 3, 6, and 12 months using modified USPHS criteria. At 6 months, the recall rate was 100%. The retention rate was 84.2% for restorations with prior acid etching, but statistically significant differences were observed between baseline and 6 months. Without acid etching, the retention rate was 77%, and no statistically significant difference was noted between 3 and 6 months. Marginal integrity (93.7% with and 87.7% without acid etching) and discoloration (95.3% with and 92.9% without acid etching) were scored as Alpha or Bravo, with better results after acid etching. After one year, the recall rate was 58.06%. Loss of pulp vitality, postoperative sensitivity, or secondary caries were not observed. After one year retention rate was of 90.6% and 76.9% with and without acid conditioning. Optibond All-in-One performs at a satisfactory clinical performance level for restoration of NCCLs after 12 months especially after acid etching.